Behaviour and emotion for sustainable product design: a review - Perrone, Carolina Cruz (2021)
Design for Sustainable Behavior focuses on how products can be designed so that users behave in a more sustainable way. User behavior is also associated with emotional interaction with products. This article aims to identify, through a systematic review of the literature, the scope of research addressing user behavior in the development of products for sustainability and the approach of emotion in this context. Also, what aspects of sustainability and types of products are lacking in the scope of research.